Policy credibility and alternative approaches to disinflation. Issue 3 (September 2017) - Bordo, Michael; Erceg, Christopher; Levin, Andrew; Michaels, Ryan
Abstract: This paper examines how central bank credibility affects the merits of a "gradualist" versus "cold turkey" approach to disinflation in a DSGE model in which private agents use optimal filtering to infer the central bank's nominal anchor. Our analysis is applied to two episodes of sharp and deliberate monetary tightening in the United States – the post-WWI deflation and the Volcker disinflation. For a policy regime with relatively high credibility, our analysis highlights the benefits of a gradualist approach; thus, the aggressive tightening that occurred in 1920–21 did not seem warranted. In contrast, for a policy regime with relatively low credibility (such as the Federal Reserve in late 1980), an aggressive policy stance can play an important signalling role by making the policy shift more evident to private agents.